Innovation in judicial services: a study of innovation models in labor courts - Michele Machado; Marcos Sousa; Vicente Rocha; Antonio Isidro (Innovation & Management Review, 2018)
Purpose - The purpose of this study is to identify innovation models in the judiciary according to the current integrated theoretical approach for innovation in services. Design/methodology/approach - This study uses a quantitative approach. The authors collected the data through a questionnaire sent to labor court public servants and judges in a Regional Labor Court in the Midwestern region of Brazil. They performed a principal component analysis to identify the factors to map the innovation models present in the court. Findings - Two factors were obtained from the results, which describe innovations in processes and services in the court studied. In terms of the examples of innovations cited by the respondents, one may note that those related to information and communications technology are the most remembered, especially the introduction of the electronic lawsuit. Originality/value - The results can contribute toward a deeper understanding of which vectors of service innovation are affected as well as the nature of the court’s underlying structure. Also, the research instrument used allows the identification and analysis of the innovation model for services and thus contributes to its validation.